Analisis Jejak Karbon Aktivitas Ekonomi Berbasis Platform Digital di Negara Berkembang - Muhammad Faizul; Rani Fadhalia; Riska Marta Hukmi (Trends Research of Environmental Studies, 2025)
The expansion of digital platform-based economic activities has become a major driver of economic growth in developing countries. However, their environmental implications, particularly in relation to carbon footprints, remain complex. This study aims to analyze the carbon footprint of digital platform-based economic activities in developing countries by examining the roles of information and communication technology infrastructure, data-intensive digital activities, platform-based transportation, and the dynamics of the digital economy and the gig economy. This study employs a quantitative approach using a cross-country empirical design based on panel data. The analysis examines the relationship between digital economy intensity and carbon emissions and identifies the mechanisms influencing this relationship. The results indicate that at early stages of digital economy development, increased platform-based activity is associated with higher carbon emissions due to rising energy consumption in digital infrastructure and transportation sectors. However, at more advanced levels of digitalization, platform-based economic activities have the potential to reduce carbon emission intensity through efficiency gains, technological innovation, and optimization of economic processes. These findings demonstrate that the environmental impact of the digital economy is conditional and strongly influenced by energy structures, infrastructure quality, and policy frameworks in developing countries. This study contributes by proposing an integrated analytical framework to understand the relationship between the platform economy and carbon footprints. The policy implications emphasize the importance of integrating digital economic development with energy transition strategies and low-carbon development pathways to ensure long-term environmental sustainability.